2010
DOI: 10.3928/00485713-20101022-05
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation and Management of Posttraumatic Cognitive Impairments

Abstract: Psychiatrists are increasingly called upon to care for individuals with cognitive, emotional, and behavioral disturbances after TBI, especially in settings serving military service personnel and Veterans. In both the early and late post-injury periods, cognitive impairments contribute to disability among persons with TBI and are potentially substantial sources of suffering for persons with TBI and their families. In this article, the differential diagnosis, evaluation, and management of posttraumatic cognitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 70 publications
1
15
0
Order By: Relevance
“…The experts regularly reported that impairments involving impulsivity, irritability, and lack of frustration tolerance were present in the daily life of patients after TBI. These answers correlate with the evidence of previous studies [28] in which disability levels among persons with TBI was shown to be highly related to cognitive impairment and that these types of impairment were a substantial source of familial stress [29]. The lack of participation in normal routine activities is therefore an important aspect of functioning or lack thereof after TBI.…”
Section: Discussionsupporting
confidence: 85%
“…The experts regularly reported that impairments involving impulsivity, irritability, and lack of frustration tolerance were present in the daily life of patients after TBI. These answers correlate with the evidence of previous studies [28] in which disability levels among persons with TBI was shown to be highly related to cognitive impairment and that these types of impairment were a substantial source of familial stress [29]. The lack of participation in normal routine activities is therefore an important aspect of functioning or lack thereof after TBI.…”
Section: Discussionsupporting
confidence: 85%
“…Reported predictors of impaired executive functioning following early frontal lobe lesions include younger age at injury (Anderson, Brown, Newitt, & Hoile, 2011;Anderson, Catroppa, Morse, Haritou, & Rosenfeld, 2000), injury severity (Anderson et al, 2000, associated epilepsy (Arciniegas, Frey, Newman, & Wortzel, 2010), as well as lower socioeconomic status (SES) (Anderson, 2009). The association between IQ and EFs in children has rarely been investigated.…”
Section: Introduction Executive Functionsmentioning
confidence: 99%
“…Given the study participants' mTBI diagnoses and their reported needs and cognitive deficits, it is possible that their cognitive deficits are limiting their development and use of strategies (Figure 1) [3,5,[17][18][19]. It is possible that the lack of spontaneous suggestions from the participants might be a result of the mental status at the time they were interviewed.…”
Section: Strategies and Advicementioning
confidence: 99%
“…These cognitive difficulties are likely to hamper successful reintegration of Veterans with TBI. To make matters worse, the VA faces challenges in screening and evaluating servicemembers for mTBI because the symptoms of mTBI often mirror those of other disorders such as posttraumatic stress disorder (PTSD), depression, anxiety disorder, and adjustment disorder, all of which can also exist within the context of TBI [5,7,15,[18][19][20][21]. Even Veterans with mTBI can experience cognitive difficulties compounded by other disorders that can hamper successful reintegration into society after combat [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%